Nursing Students’ Intention to Work in Rural Areas after Graduation: A Mixed Approach Study - Siwakoti, Selina; Gahatraj, Nanda Ram; Shrestha, Niranjan (Journal of Karnali Academy of Health Sciences, 2023)
Background: A key issue of Human Resources for Health and constraint to Universal Health Coverage is an inequitable distribution of healthcare workers between rural and urban areas. The accessibility to health services has been found difficult in rural areas due to shortage of health workers. As final-year nursing students are the prospective human resource for health, this study aimed to assess the intention of nursing students to work in rural areas and identify the motivating and discouraging factors associated with their intention. Methods: A cross-sectional study with mixed methods was conducted among final-year bachelor-level nursing students of Pokhara, Nepal from December 2019 to July 2020. A census method using a self-administered questionnaire was used for the quantitative method and in-depth interviews were conducted for the qualitative method. Descriptive and inferential statistics for quantitative and content analysis for the qualitative method were performed. Results: One-third (33.3%) of the participants had the intention to work in rural areas. The motivating factors were an opportunity for career advancement (AOR: 3.8; 95% CI: 1.35-10.77), locating near to family (AOR: 3.58, 95% CI: 1.36-9.45), high salary/incentives, and high healthcare needs in rural areas; whereas discouraging factors were isolation from family and friends (AOR 4.10, 95% CI 1.34-12.52), less availability of recreational facilities (AOR 3.68, 95% CI 1.11-12.21), inadequate salary/incentives, lack of equipment and resources, low utilization of skills and knowledge and low self-perceived competency. Conclusion: Only one-third of the participants had the intention to work in rural areas. The participants preferred to work staying with or nearby their family. The enrollment of students of rural origin/residence or background in a nursing program should be ensured. Various motivating factors like training, attractive incentives, infrastructures, and facilities should be offered to make rural jobs more attractive.